Genomic and Transcriptomic Insight of Giant Sclerotium Formation of Wood-Decay Fungi - Cao, Shuo; Yang, Yang; Bi, Guiqi; Nelson, David; Hu, Sheng; Makunga, Nokwanda Pearl; Yu, Bin; Liu, Xin; Li, Xiaohua; Hu, Xuebo (Frontiers in Microbiology, 2021)
Many fungi form persistent and dormant sclerotia with compact hardened mycelia during unfavorable circumstances. While most of these sclerotia are small in size, Wolfiporia cocos, a wood decay fungus, grows into giant sclerotia, which are mainly composed of polysaccharides of linear (1→3)-β-D-glucan. To explore the underlying mechanism of converting sophisticated wood polysaccharides for biosynthesis of highly homogenized glucans in W. cocos, we sequenced and assembled the genome of a cultivated W. cocos strain (WCLT) in China. The 62 Mb haploid genome contains 44.2% repeat sequences, of which, 48.0% are transposable elements (TEs). Contrary to the genome of W. cocos from North America, WCLT has independently undergone a whole genome duplication (WGD) event. The large scale TEs insertion and WGD occurrence overlapped an archaeological Pleistocene stage with low oxygen and high temperature and these stresses might have induced sclerotium differences due to geographical distribution. Wood decomposition enzymes, as well as sclerotium-regulator kinase, aquaporins and highly expanded gene families such as NAD related families, together with actively expressed 1,3-β-glucan synthase for sclerotium polysaccharides, all have contributed to the sclerotium formation and expanding. This genomic study inspires further exploration on how fungi converting wood into simple glucans in the sclerotium of W. cocos.